Analysis of Mathematical Investigations of Learners in Terms of Personality Type - Nurhayati, Elis; Nurandini, Meti (International Journal of Mathematics and Mathematics Education (IJMME), 2023)
This study aims to analyze the mathematical investigation process of students in terms of extrovert personality types and introvert personality types. The method used in this research is descriptive qualitative method. Data was collected using think aloud when students worked on the mathematical investigation process test questions. The research subjects were 4 people taken from class VII students at SMP Negeri 3 Kawali. The results of this study show that students with extroverted personality types can understand problems in their own language briefly, pose problems in general, are able to specialize, make assertive and confident assumptions, prove conjectures inaccurately and in less detail, make generalizations with the results inaccurate, do not re-check the results obtained and have not been able to be in the expansion stage. As for the Introvert Personality Type, they can understand problems in their own language in detail and coherently, present problems in detail, be able to specialize clearly, make conjectures carefully, prove conjectures carefully and in detail, make generalizations with appropriate results, make re-checking of the results obtained, and less able in the expansion stage.